Optical glass and optical element

A tailored glass composition with controlled oxide contents achieves high refractive index, low dispersion, and low glass transition temperature, addressing the limitations of existing optical glasses for precision pressing and optical element manufacturing.

CN119219327APending Publication Date: 2024-12-31HOYA CORPORATION +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410834648.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-11
Filing Date
2024-06-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing optical glasses lack a combination of high refractive index, low dispersion, and low glass transition temperature, which are essential for precision pressing and optical element manufacturing.

Method used

A specific glass composition with controlled contents of B2O3, ZnO, Li2O, Y2O3, and rare earth oxides (La2O3, Gd2O3) within defined ranges, along with minimal Ta2O5, Nb2O5, Bi2O3, TiO2, and WO3, to achieve refractive index of 1.750-1.790 and Abbe number of 47.5-50.5, while maintaining a glass transition temperature below 640°C.

Benefits of technology

The solution provides optical glass with enhanced optical properties for precision pressing, reducing surface damage and mold degradation, and enabling high-quality optical elements like lenses and diffraction gratings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219327A_ABST
    Figure CN119219327A_ABST
Patent Text Reader

Abstract

Provided is an optical glass having a high refractive index, low dispersivity, and a low glass transition temperature. In a glass composition expressed in mass%, the optical glass has a B2O3 content of 15.00 mass% or more and 33.00 mass% or less, a ZnO content of 6.00 mass% or more and 18.00 mass% or less, a Li2O content of more than 0.00 mass%, a Y2O3 content of 3.00 mass% or more and 23.00 mass% or less, a total content of Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3 (Ta2O5 + Nb2O5 + Bi2O3 + TiO2 + WO3) of 0.00 mass% or more and 0.30 mass% or less, and a total content of B2O3, ZnO, Bi2O3, TiO2 and WO3 of 0.00 mass% or more and 0.30 mass% or less. The total content RE of La2O3, Gd2O3 and Y2O3 is 43.00 mass% or more and 58.00 mass% or less, the mass ratio of the total content RE to the total content of ZrO2, Ta2O5, Nb2O5 and WO3 (RE / (ZrO2 + Ta2O5 + Nb2O5 + WO3)) is 2.00 or more and 13.00 or less, the mass ratio of the total content RE to the ZnO content (RE / ZnO) is 3.80 or more, the refractive index nd of the optical glass is 1.750 or more and 1.790, and the Abbe number vd of the optical glass is 47.5 or more and 50.5 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to optical glass and optical elements. Background Art

[0002] In recent years, various optical glasses have been proposed as materials for optical elements (see, for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-065747 Summary of the invention

[0006] Problems to be solved by the invention

[0007] Among optical glasses, optical glasses having a high refractive index and low dispersion are useful as materials for optical elements.

[0008] One of the properties desired for optical glass is a low glass transition temperature Tg. Low Tg glass is preferred because it has excellent suitability for precision pressing, for example.

[0009] An object of one embodiment of the present invention is to provide an optical glass having a high refractive index and low dispersion and a low glass transition temperature.

[0010] Solutions to the problem

[0011] One embodiment of the present invention relates to an optical glass, wherein:

[0012] In the glass composition expressed in mass %,

[0013] The B2O3 content is 15.00 mass % or more and 33.00 mass % or less,

[0014] The ZnO content is 6.00 mass % or more and 18.00 mass % or less,

[0015] Li2O content exceeds 0.00% by mass,

[0016] The Y2O3 content is 3.00 mass % or more and 23.00 mass % or less,

[0017] The total content of Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3 (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is 0.00 mass% or more and 0.30 mass% or less,

[0018] The total content RE of La2O3, Gd2O3 and Y2O3 is 43.00 mass % or more and 58.00 mass % or less,

[0019] The mass ratio of the total content RE to the total content of ZrO2, Ta2O5, Nb2O5 and WO3 (RE / (ZrO2+Ta2O5+Nb2O5+WO3)) is 2.00 or more and 13.00 or less,

[0020] The mass ratio of the total content RE to the content of ZnO (RE / ZnO) is 3.80 or more.

[0021] The optical glass has a refractive index nd of 1.750 or more and 1.790, and an Abbe number νd of 47.5 or more and 50.5 or less.

[0022] Effects of the Invention

[0023] According to one embodiment of the present invention, an optical glass having a high refractive index, low dispersion, and a low glass transition temperature can be provided. In addition, according to one embodiment of the present invention, an optical element made of the optical glass can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A cross-sectional schematic diagram of a precision press molding apparatus is shown. DETAILED DESCRIPTION

[0025] [Optical glass]

[0026] In the present invention and this specification, the glass composition is expressed by the glass composition based on oxides. Here, the "glass composition based on oxides" refers to the glass composition obtained by converting the glass raw materials into substances that are completely decomposed during melting and exist in the glass in the form of oxides. In addition, unless otherwise specified, the glass composition is expressed on a mass basis (mass %, mass ratio).

[0027] The glass composition in the present invention and this specification can be obtained by methods such as ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). For example, quantitative analysis is performed on each element separately using ICP-AES. Then, the analysis value is converted into oxide expression. The analysis value based on ICP-AES sometimes contains a measurement error of, for example, about ±5% of the analysis value. Therefore, the value expressed by the oxide converted from the analysis value sometimes also contains an error of about ±5%.

[0028] In addition, in the present invention and this specification, the content of a constituent component is 0.00% or is not contained or introduced, which means that the constituent component is substantially not contained, and means that the content of the constituent component is below the impurity level. Below the impurity level means, for example, less than 0.01%. "0%" can mean, for example, "0.0%" or "0.00%".

[0029] In the present invention and this specification, the refractive index refers to the refractive index nd under helium d-ray (wavelength 587.56 nm).

[0030] In the present invention and this specification, the Abbe number νd is used as a value indicating a property related to dispersion, and is represented by the following mathematical formula.

[0031] νd=(nd-1) / (nF-nC)

[0032] In the above formula, nF is the refractive index under the F ray of blue hydrogen (wavelength 486.13nm), and nC is the refractive index under the C ray of red hydrogen (656.27nm).

[0033] Hereinafter, the above-mentioned optical glass (may be simply referred to as "glass") will be described in more detail.

[0034] <Glass composition>

[0035] The content of Li2O exceeds 0.00%. Li2O is a component that can suppress the decrease in refractive index and lower the glass transition temperature, and is therefore an essential component in the above optical glass. The content of Li2O is preferably 0.025% or more, and more preferably 0.050% or more, 0.075% or more, 0.10% or more, 0.15% or more, and 0.20% or more.

[0036] The upper limit of the Li2O content is not particularly limited, and may be, for example, 2.30% or less, preferably 2.20% or less, and more preferably 2.10% or less, 2.08% or less, 2.06% or less, 2.04% or less, 2.02% or less, 2.00% or less, 1.98% or less, 1.96% or less, and 1.94% or less in the order of more preferred.

[0037] In Li2O, Na2O, K2O and Cs2O which are alkali metal oxides, the Li2O content is as described above.

[0038] The respective contents of Na2O, K2O and Cs2O may be, for example, 0.00%, 0.00% or more, or more than 0.00%. In addition, for example, the respective contents may be 5.00% or less, 4.00% or less, 3.00% or less, 2.00% or less, 1.00% or less, 0.50% or less, 0.40% or less, 0.30% or less, 0.20% or less, or 0.10% or less.

[0039] B2O3 is a network-forming component of glass and is a component that helps maintain the thermal stability and solubility of glass. Therefore, the B2O3 content is 15.00% or more, preferably 16.00% or more, and more preferably 17.00% or more, 18.00% or more, 18.50% or more, 19.00% or more, 19.25% or more, 19.50% or more, 19.75% or more, 20.00% or more, 20.25% or more, 20.50% or more, 20.75% or more, 21.00% or more, 20.25% or more, and 21.30% or more.

[0040] B2O3 is also a component that lowers the refractive index of the glass if more of it is contained in the glass. Therefore, the B2O3 content is 33.00% or less, preferably 32.00% or less, and more preferably in the order of 31.50% or less, 31.00% or less, 30.75% or less, 30.50% or less, 30.25% or less, 30.00% or less, 29.75% or less, 29.50% or less, 29.25% or less, and 29.00% or less.

[0041] SiO2 is also a network-forming component of glass, and is a component that helps maintain the thermal stability and solubility of glass. Considering this point, SiO2 content is preferably more than 0.00%, more preferably more than 0.20%, and more preferably in the order of more than 0.40%, more than 0.60%, more than 0.65%, more than 0.70%, more than 0.75%, more than 0.80%, more than 0.85%, more than 0.90%, more than 0.95%, more than 1.00%, more than 1.05%, more than 1.10%, more than 1.15%, more than 1.20%, more than 1.23%.

[0042] SiO2 is also a component that lowers the refractive index of the glass if more SiO2 is contained in the glass. Therefore, the SiO2 content is preferably 13.00% or less, and more preferably in the order of 12.00% or less, 11.00% or less, 10.75% or less, 10.50% or less, 10.25% or less, 10.00% or less, 9.80% or less, 9.60% or less, 9.40% or less, 9.20% or less, 9.00% or less, 8.80% or less, 8.60% or less, 8.40% or less, and 8.30% or less.

[0043] P2O5 is also a network-forming component of glass and contributes to maintaining the thermal stability and solubility of glass. The lower limit of the P2O5 content is not particularly limited, and may be, for example, 0.00%, 0.00% or more, or more than 0.00%.

[0044] P2O5 is also a component that lowers the refractive index of the glass if more of it is contained in the glass. Therefore, the P2O5 content is preferably 3.00% or less, more preferably 2.50% or less, further preferably 2.00% or less, and further preferably in the order of 1.75% or less, 1.50% or less, 1.40% or less, 1.30% or less, 1.20% or less, 1.20% or less, and 1.15% or less.

[0045] The mass ratio of Li2O content to SiO2 content (Li2O / SiO2) is preferably 1.00 or less, more preferably 0.90 or less, and preferably 0.80 or less, 0.70 or less, 0.68 or less, 0.66 or less, 0.64 or less, 0.62 or less, 0.60 or less, 0.58 or less, 0.56 or less, and 0.54 or less. As for the lower limit, it may exceed 0.00, preferably 0.01 or more, and preferably 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, and 0.10 or more.

[0046] The mass ratio (Li2O / SiO2) is preferably the above lower limit from the viewpoint of lowering the glass transition temperature, and is preferably the above upper limit from the viewpoint of suppressing the increase in the glass transition temperature and maintaining thermal stability.

[0047] The La2O3 content is preferably above 20.00%, and is more preferably in the order of above 21.00%, above 22.00%, above 23.00%, above 24.00%, above 25.00%, above 26.00%, above 27.00%, above 28.00%, above 28.50%, above 29.00%, above 29.50%, above 30.00%, above 30.50%, above 31.00%, above 31.50%, above 32.00%, above 32.50%, and above 33.00%.

[0048] The La2O3 content is preferably less than 50.00%, and is more preferably less than 49.00%, less than 48.00%, less than 47.00%, less than 46.00%, less than 45.00%, less than 44.50%, less than 44.00%, less than 43.50%, less than 43.00%, less than 42.50%, less than 42.00%, less than 41.75%, and less than 41.60% in the order of less than 49.00%, less than 48.00%, less than 47.00%, less than 46.00%, less than 45.00%, less than 44.50%, less than 44.00%, less than 43.50%, less than 43.00%, less than 42.50%, less than 42.00%, less than 41.75%, and less than 41.60%.

[0049] The Gd2O3 content may be, for example, 0.00%, 0.00% or more, or more than 0.00%. The upper limit is preferably 7.50% or less, and more preferably 6.50% or less, 5.50% or less, 5.00% or less, 4.50% or less, 4.00% or less, 3.50% or less, 3.00% or less, 2.80% or less, 2.60% or less, and 1.25% or less.

[0050] Y2O3 is a component that can improve thermal stability by containing a given amount in glass.

[0051] From the viewpoint of improving the thermal stability of the glass, the Y2O3 content is 3.00% or more, preferably 4.00% or more, and more preferably 5.00% or more, 6.00% or more, 6.50% or more, 7.00% or more, 7.50% or more, 8.00% or more, 8.50% or more, 8.75% or more, 9.00% or more, 9.25% or more, and 9.50% or more.

[0052] In addition, from the viewpoint of improving the thermal stability of the glass, the Y2O3 content is less than 23.00%, preferably less than 22.50%, and more preferably less than 22.00%, less than 21.50%, less than 21.00%, less than 20.50%, less than 20.00%, less than 19.50%, less than 19.00%, less than 18.50%, less than 18.25%, less than 18.00%, and less than 17.75%.

[0053] Regarding rare earth components, La2O3, Gd2O3 and Y2O3 are components that can increase the refractive index while maintaining low dispersion. From the viewpoint of maintaining or improving the thermal stability of the glass, the content of each rare earth oxide is preferably within the above range.

[0054] The total content of La2O3, Gd2O3 and Y2O3 is also expressed as "RE".

[0055] From the viewpoint of maintaining a high refractive index and low dispersion, RE is 43.00% or more, preferably 43.50% or more, and more preferably 44.00% or more, 44.50% or more, 45.00% or more, 45.50% or more, 46.00% or more, 46.50% or more, 47.00% or more, 47.50% or more, 48.00% or more, 48.50% or more, 49.00% or more, 49.25% or more, 49.50% or more, and 49.75% or more.

[0056] In addition, from the viewpoint of maintaining or improving the thermal stability of the glass, RE is less than 58.00%, preferably less than 57.50%, and more preferably less than 57.00%, less than 56.50%, less than 56.00%, less than 55.50%, less than 55.18%, less than 55.00%, less than 54.75%, less than 54.50%, less than 54.25%, less than 54.00%, and less than 53.75%.

[0057] The ZnO content is 6.00% or more, preferably 6.50% or more, more preferably 7.00% or more, 7.25% or more, 7.50% or more, 7.75% or more, 8.00% or more, 8.20% or more, 8.40% or more, 8.60% or more, and 8.75% or more. The upper limit is 18.00% or less, preferably 17.50% or less, and more preferably 17.00% or less, 16.50% or less, 16.00% or less, 15.50% or less, 15.00% or less, 14.50% or less, 14.00% or less, 13.75% or less, 13.50% or less, and 13.25% or less.

[0058] ZnO is a component that suppresses the reduction of refractive index, reduces the glass transition temperature, and improves melting property. On the other hand, if it is contained in a large amount in glass, it will cause the liquidus temperature to become higher and the thermal stability of the glass to decrease. Considering from these viewpoints, the ZnO content is preferably in the above range.

[0059] From the viewpoint of further increasing the glass transition temperature, the total content of Li2O and ZnO (Li2O+ZnO) is preferably 7.00% or more, and more preferably in the order of 8.00% or more, 8.50% or more, 9.00% or more, 9.25% or more, and 9.50% or more. As for the upper limit, from the viewpoint of maintaining or improving the thermal stability of the glass, it is preferably 19.00% or less, and more preferably in the order of 18.50% or less, 18.00% or less, 17.50% or less, 17.00% or less, 16.50% or less, 16.25% or less, 16.00% or less, 15.75% or less, 15.50% or less, and 15.20% or less.

[0060] The ZrO2 content may be 0.00%, 0.00% or more, or more than 0.00%, preferably 3.00% or more, more preferably 3.50% or more, 4.00% or more, 4.25% or more, 4.50% or more, 4.64% or more, 4.75% or more, 5.00% or more, 5.10% or more. As for the upper limit, it is preferably 10.00% or less, and 9.50% or less, 9.00% or less, 8.75% or less, 8.50% or less, 8.25% or less, 8.00% or less, 7.90% or less. 7.80% or less, 7.70% or less, 7.60% or less, 7.50% or less, 7.40% or less, 7.30% or less are more preferred.

[0061] By introducing ZrO2 into the glass, the effect of improving the thermal stability of the glass can be obtained without causing the refractive index of the glass to decrease, so the above optical glass preferably contains ZrO2. On the other hand, if the content of ZrO2 increases, it will cause a rise in the melting temperature. Considering from these viewpoints, the ZrO2 content is preferably in the above range.

[0062] The total content of Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3 (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is 0.00% or more, and may be 0.00%. The upper limit is 0.30% or less, preferably 0.25% or less, and more preferably 0.20% or less, 0.15% or less, 0.10% or less, 0.08% or less, 0.06% or less, 0.04% or less, 0.02% or less, and 0.00% or less.

[0063] The total content (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is preferably the above upper limit from the viewpoint of maintaining the thermal stability of the glass. In addition, Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3 tend to react with the molding surface of the molding die during press molding, resulting in a deterioration in the surface quality of the glass, and sometimes the coloring of the glass is enhanced. Therefore, it is most preferred that the optical glass does not contain Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3, that is, the total content (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is 0.00%.

[0064] The respective contents of Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3 are preferably less than 0.30%, more preferably less than 0.25%, and are further preferably less than 0.20%, less than 0.15%, less than 0.10%, less than 0.08%, less than 0.06%, less than 0.04%, less than 0.02% in this order, and are most preferably 0.00%.

[0065] The mass ratio of the total content RE of La2O3, Gd2O3 and Y2O3 to the total content of ZrO2, Ta2O5, Nb2O5 and WO3 (RE / (ZrO2+Ta2O5+Nb2O5+WO3)) is above 2.00, preferably above 3.00, and more preferably above 4.00, above 4.20, above 4.40, above 4.60, above 4.80, above 5.00, above 5.20, above 5.40, above 5.60, above 5.80, above 6.00, above 6.20, above 6.40, above 6.60 and above 6.80 in the order of above. The upper limit is 13.00 or less, preferably 12.00 or less, and more preferably 11.80 or less, 11.60 or less, 11.40 or less, 11.20 or less, 10.00 or less, 10.90 or less, 10.80 or less, 10.70 or less, 10.60 or less, and 10.50 or less in this order.

[0066] Regarding the mass ratio (RE / (ZrO2+Ta2O5+Nb2O5+WO3)), from the viewpoint of maintaining low dispersion of the glass, the above-mentioned lower limit is preferably used, and from the viewpoint of maintaining thermal stability, the above-mentioned upper limit is preferably used.

[0067] The mass ratio (RE / ZnO) of the total content RE of La2O3, Gd2O3 and Y2O3 to the content of ZnO is 3.80 or more, preferably 3.81 or more, and more preferably 3.82 or more. There is no particular limitation on the upper limit, for example, it is preferably 9.00 or less, and more preferably in the order of 8.50 or less, 8.00 or less, 7.50 or less, 7.00 or less, 6.80 or less, 6.60 or less, 6.40 or less, 6.20 or less, 6.00 or less, and 5.95 or less.

[0068] The mass ratio (RE / ZnO) is preferably within the above lower limit from the viewpoint of maintaining low dispersion of the glass, and is preferably within the above upper limit from the viewpoint of maintaining a low glass transition temperature.

[0069] The optical glass may contain one or more of the alkaline earth metal oxides, or may not contain any of them. In the optical glass, the content of each of MgO, CaO, SrO and BaO may be, for example, 0.00%, 0.00% or more, more than 0.00%, 0.01% or more, 0.10% or more, or 0.50% or less, or, for example, 3.00% or less, 2.00% or less, or 1.00% or less.

[0070] Sb2O3 is a component that can be added as a clarifier. From the viewpoint of suppressing damage to the molding surface of the pressing mold during precision pressing and from the viewpoint of suppressing the coloring of the glass, the less the amount added, the better. As for the Sb2O3 content, in the glass composition expressed in mass%, the Sb2O3 content expressed as the added ratio (the Sb2O3 content when the total mass of the glass components other than Sb2O3 is set to 100 mass%) is preferably in the order of more than 0.00%, more than 0.01%, and more than 0.02%. In addition, it is preferably in the order of less than 1.00%, less than 0.90%, less than 0.80%, less than 0.70%, less than 0.60%, less than 0.50%, less than 0.40%, less than 0.30%, less than 0.20%, and less than 0.10%.

[0071] SnO2 can also be added as a clarifier. If it is added in an external addition ratio exceeding 1.00%, it will cause the glass to be colored, or when the glass is heated, softened, and re-molded by press molding, Sn will become the starting point of crystal nucleation and produce a tendency to devitrification. Therefore, it is preferred that the amount of SnO2 added is 0.00% or more and 1.00% or less, more preferably 0.00% or more and 0.50% or less, and particularly preferably not added. The SnO2 content based on the external addition ratio refers to the content of SnO2 expressed in mass % when the total content of the glass components other than SnO2 is set to 100 mass %.

[0072] The optical glass can be made without containing components such as Lu and Hf. Lu and Hf are expensive components, so it is preferred to suppress the content of Lu2O3 and HfO2 to 0.00% or more and 2.00% or less, more preferably to suppress it to 0.00% or more and 1.00% or less, further preferably to suppress it to 0.00% or more and 0.80% or less, further preferably to suppress it to 0.00% or more and 0.10% or less, and it is particularly preferred not to introduce Lu2O3 and not to introduce HfO2.

[0073] In addition, considering the environmental influence, it is preferable not to introduce Pb, and it is also preferable not to introduce As, U, Th, Te, and Cd.

[0074] Furthermore, from the viewpoint of effectively utilizing the excellent light transmittance of glass, it is preferred not to introduce substances that are main causes of coloration, such as Cu, Cr, V, Fe, Ni, and Co.

[0075] <Glass Properties>

[0076] (Glass transition temperature Tg)

[0077] The optical glass can have a low glass transition temperature Tg by having the above glass composition. For example, from the perspective of producing an optical element without scratches, blurring and damage on the surface by precision press molding, low Tg glass is preferred. In addition, from the perspective of suppressing the degradation of the release film in precision press molding, suppressing the consumption of the press molding mold, etc., low Tg glass is preferred. The Tg of the above optical glass is preferably less than 640°C, and is more preferably in the order of 638°C or less, 636°C or less, 634°C or less, 632°C or less, 630°C or less, 628°C or less, 626°C or less, 624°C or less, 622°C or less, and 620°C or less. The lower limit of Tg is not particularly limited, for example, it can be 530°C or more, and can also be 540°C or more, 550°C or more, 555°C or more, 560°C or more, 565°C or more, or 570°C or more. The glass transition temperature Tg can be obtained by the method described below.

[0078] (Refractive index nd)

[0079] High refractive index glass is useful as a material for optical elements. The refractive index nd of the optical glass is 1.7500 or more, preferably 1.7530 or more, more preferably 1.7550 or more, 1.7570 or more, 1.7590 or more, 1.7610 or more, 1.7630 or more, and 1.7632 or more. The upper limit is 1.7900 or less, preferably 1.7910 or less, and more preferably 1.7890 or less, 1.7870 or less, 1.7850 or less, 1.7830 or less, 1.7810 or less, 1.7790 or less, 1.7770 or less, and 1.7760 or less.

[0080] (Abbe number νd)

[0081] Glass showing low dispersion is useful as a material for optical elements. The Abbe number νd of the optical glass is 47.50 or more, preferably 48.20 or more, more preferably 48.30 or more, 48.35 or more, 48.40 or more, 48.45 or more, 48.50 or more, 48.55 or more, 48.60 or more, 48.65 or more, and 48.70 or more. The upper limit is 50.50 or less, preferably 50.20 or less, and more preferably 50.15 or less, 50.10 or less, 50.05 or less, 50.00 or less, 49.95 or less, 49.90 or less, and 49.86 or less.

[0082] When considering glass as a material for optical elements, increasing the refractive index of glass is equivalent to expanding the degree of freedom possessed by glass. From the viewpoint of expanding the above-mentioned degree of freedom, increasing the refractive index is preferred. On the other hand, if dispersion is maintained and the refractive index is increased, a tendency of reduced glass stability will be generated. From these viewpoints, the Abbe number vd is preferably in the above-mentioned range.

[0083] (Coloring degree λ5, λ 80 )

[0084] Regarding the light transmittance of the glass, more specifically, the suppression of the long wavelength of the light absorption end on the short wavelength side, the coloring degree λ5 and λ 80 The coloration degree λ5 refers to the wavelength at which the spectral transmittance (including surface reflection loss) of glass with a thickness of 10 mm from the ultraviolet region to the visible region reaches 5%. 80 The wavelength at which the spectral transmittance reaches 80% as measured by the method described for λ5 is shown in the table below. 80 The spectral transmittance T (%) of the glass in the present invention and this specification can be expressed as follows: For a glass sample having two parallel planes after optical polishing, the intensity of light perpendicularly incident on one of the planes is set to I in , and the intensity of the light emitted from the other side after passing through the glass sample is set to I out When T(%)=I out / I in ×100 indicates.

[0085] According to the chromaticity λ5 and λ 80 , the absorption end on the short wavelength side of the spectral transmittance can be quantitatively evaluated. When lenses are bonded together by ultraviolet curing adhesives to make bonded lenses, the following operation can be performed: ultraviolet rays are irradiated to the adhesive through the optical element to cure the adhesive. From the perspective of efficiently curing the ultraviolet curing adhesive, it is preferred that the absorption end on the short wavelength side of the spectral transmittance is in the short wavelength range. As an indicator for quantitatively evaluating the absorption end on the short wavelength side, the coloring degree λ5 and λ 80 One or more of.

[0086] The optical glass may preferably exhibit a λ5 of 320 nm or less. λ5 is more preferably 310 nm or less, 300 nm or less, and 290 nm or less in this order. The shorter the wavelength of λ5, the more preferred it is, and the lower limit is not particularly limited.

[0087] The optical glass preferably exhibits a λ of less than 510 nm. 80 . 80More preferably, the wavelength is 400 nm or less, 390 nm or less, 380 nm or less, and 377 nm or less in this order. 80 The shorter the wavelength, the more preferred, and the lower limit is not particularly limited.

[0088] <Glass Manufacturing Method>

[0089] The optical glass can be obtained as follows: oxides, carbonates, sulfates, nitrates, hydroxides, etc. as raw materials are weighed and mixed in a manner to obtain a target glass composition, and they are fully mixed to form a mixed batch, which is heated and melted in a melting container such as a platinum container, and deaerated and stirred to produce a homogeneous and bubble-free molten glass, which is molded to obtain the optical glass. Specifically, it can be produced by a known melting method.

[0090] As described above, if the content of ZrO2 increases, the melting temperature will rise. On the other hand, when a platinum container is used as a melting container, if the melting temperature becomes high, Pt ions will be eluted from the platinum container, and the transmittance will deteriorate, thus causing the above-mentioned coloring degrees λ5 and λ 80 Therefore, the above coloring degrees λ5 and λ 80 From the viewpoint of shortening the wavelength, the melting temperature is preferably low (for example, 1000° C. or higher and 1300° C. or lower). In addition, from this point of view, the content of ZrO 2 is preferably within the range described above.

[0091] [Glass material for press molding, method for producing the same, and method for producing a glass molded body]

[0092] According to the embodiments of the present invention, there can be provided a press-molding glass material made of the above optical glass, a glass molded body made of the above optical glass, and methods for producing the same.

[0093] The press-molding glass material refers to a glass block to be heated and subjected to press molding.

[0094] Examples of press-molding glass materials include glass blocks having a mass equivalent to that of press-molded products, such as glass materials (press-molding glass gobs) used for press-molding of precision press-molding preforms and optical element blanks.

[0095] The glass raw material for press molding can be produced, for example, by a process of processing a glass molded body. The glass molded body can be produced by heating and melting the glass raw material as described above and molding the obtained molten glass. Examples of the processing method of the glass molded body include cutting, grinding, polishing, etc. In addition, an example of the production of a preform for precision press molding will be described later.

[0096] [Optical element blank and method for manufacturing the same]

[0097] According to one embodiment of the present invention, an optical element blank made of the above optical glass can be provided. The optical element blank is a glass molded body having a shape similar to the shape of the optical element to be manufactured. The optical element blank can be manufactured by a method of molding glass into a shape obtained by adding a machining allowance that will be removed by machining to the shape of the optical element to be manufactured. For example, the optical element blank can be manufactured by a method of heating and softening a glass raw material for press molding and performing press molding (reheat pressing method); a method of supplying a molten glass block to a press molding mold by a known method and performing press molding (direct pressing method), etc.

[0098] [Optical element and method of manufacturing the same]

[0099] According to one embodiment of the present invention, an optical element made of the above optical glass can be provided. As the type of optical element, lenses such as spherical lenses and aspherical lenses, prisms, diffraction gratings, etc. can be exemplified. As the shape of the lens, various shapes such as biconvex lenses, plano-convex lenses, biconcave lenses, plano-concave lenses, convex meniscus lenses, and concave meniscus lenses can be exemplified.

[0100] As one method of manufacturing an optical element, a method of manufacturing an optical element by heating a preform for precision press molding can be cited. Precision press molding can use a known press molding mold and a known molding method. The method of manufacturing an optical element using precision press molding is suitable for manufacturing aspherical lenses, micro lenses, diffraction gratings, etc.

[0101] The surface of the preform for precision press molding can be coated with a release film in order to prevent the glass from fusing with the molding surface of the press molding mold during precision press molding and to make the glass stretch along the molding surface better. Such a release film is well known. A preform for precision press molding made of low Tg glass is preferred from the viewpoint of suppressing the degradation of the release film. As an example of a release film, a carbon-containing film can be cited. The carbon-containing film can be, for example, a film with carbon as the main component (when the element content in the film is expressed in atomic %, the carbon content is greater than the content of other elements). As a film-forming method for the carbon-containing film, known methods such as vacuum evaporation method, sputtering method, ion plating method using carbon raw materials, and known methods such as thermal decomposition of material gases such as hydrocarbons can be used.

[0102] Figure 1 A schematic cross-sectional view of a precision press molding apparatus is shown. Precision press molding can be performed, for example, as follows.

[0103] A precision press molding preform (hereinafter referred to as "preform") 4 is placed between a lower mold 2 and an upper mold 1 constituting a press molding die. Then, a nitrogen atmosphere is formed in a quartz tube 11, and a heater (not shown) is energized to heat the inside of the quartz tube 11. The temperature inside the press molding die is set so that the glass to be molded shows, for example, 10 6 ~10 10 dPa·s, and while maintaining this temperature, the push rod 13 is lowered to push the upper mold 1 to press the preform set in the molding die. After the pressurization, the pressurized pressure is released, and the press-molded glass molded product is slowly cooled while being in contact with the lower mold 2 and the upper mold 1 until the viscosity of the glass reaches, for example, 10 12 dPa·s or higher, and then rapidly cooled to room temperature, and the glass molded product is removed from the molding mold. Thus, an optical element can be obtained. Figure 1 In the embodiment, the holding member 10 holds the lower mold 2 and the shell mold 3, and the support rod 9 supports the upper mold 1, the lower mold 2, the shell mold 3, and the holding member 10, and is subjected to the pressure of the push rod 13. A thermocouple 14 is inserted into the lower mold 2 to monitor the temperature inside the press molding die.

[0104] As another method for manufacturing an optical element, a method for manufacturing an optical element in which an optical element blank is machined to produce the optical element can be cited. As machining, cutting, cutting, rough grinding, fine grinding, polishing, etc. can be exemplified. Such a manufacturing method is suitable for the manufacture of spherical lenses, prisms, etc.

[0105] Example

[0106] Hereinafter, the present invention will be described in more detail with reference to the examples, but the present invention is not limited to the embodiments shown in the examples.

[0107] [Examples No. 1 to No. 154]

[0108] In order to achieve the glass composition shown in the table below, corresponding phosphates, fluorides, nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc. were used as raw materials for introducing each component, and the raw materials were weighed and fully mixed to prepare the blended raw materials. In the following table, the Sb2O3 content is expressed as the addition ratio.

[0109] The prepared raw materials were placed in a platinum crucible, heated in a furnace set at 1000-1300°C, and melted for 120 minutes. After stirring the molten glass to homogenize it, the molten glass was poured into a preheated mold, naturally cooled to near the glass transition temperature and immediately placed in an annealing furnace, kept at a temperature around the glass transition temperature for about 30 minutes, slowly cooled at a slow cooling rate of -30°C / hour for 4 hours, and then naturally cooled to room temperature in the furnace, thereby obtaining each optical glass No. 1 to No. 154 shown in the following table.

[0110] <Physical property measurement>

[0111] Various physical properties of each optical glass shown in the following table were measured by the following methods.

[0112] (1) Refractive index nd, Abbe number νd

[0113] The refractive index nd and the Abbe number νd of each optical glass were measured by the refractive index measurement method according to the Japan Optical Glass Industry Association standard.

[0114] (2) Glass transition temperature Tg

[0115] Glass was fully pulverized in a mortar or the like as a sample, and the glass transition temperature Tg was measured by a differential scanning calorimeter (DSC3300SA) manufactured by NETZSCH JAPAN Co., Ltd. using a platinum cell as a sample container at a heating rate of 10°C / min.

[0116] (3) Coloring degree λ5, λ 80

[0117] The spectral transmittance T (%) was measured using a spectrophotometer using a glass sample with two optically polished flat surfaces facing each other and having a thickness of 10 ± 0.1 mm. The wavelength (nm) at which T reached 5% was denoted as λ5, and the wavelength (nm) at which T reached 80% was denoted as λ 80 .

[0118] The above results are shown in the following table.

[0119]

[0120]

[0121]

[0122]

[0123]

[0124]

[0125]

[0126]

[0127]

[0128]

[0129]

[0130]

[0131]

[0132]

[0133]

[0134]

[0135] [Table 3-1]

[0136]

[0137] [Table 3-2]

[0138]

[0139] [Table 3-3]

[0140]

[0141] [Table 3-4]

[0142]

[0143] [Table 3-5]

[0144]

[0145] [Table 3-6]

[0146]

[0147] [Table 3-7]

[0148]

[0149] [Table 3-8]

[0150]

[0151] <Production of optical components using precision press molding>

[0152] For each of the above embodiments, in order to achieve the glass composition shown in the above table, the corresponding nitrates, sulfates, carbonates, hydroxides, oxides, borics, etc. are used as raw materials for introducing each component, and the raw materials are weighed and fully mixed to prepare the formulated raw materials.

[0153] A production example of a preform (production example 1) is described. The prepared raw materials are placed in a platinum crucible, heated, and melted. The clarified and homogenized molten glass is made to flow out at a certain flow rate from a platinum alloy pipe whose temperature is adjusted to a temperature range where it can flow out stably without causing glass devitrification, and is separated into molten glass blocks of the mass of the target preform by dripping or descending cutting. The separated molten glass blocks are received by a mold having a gas outlet at the bottom, and a preform for precision press molding is formed while gas is ejected from the gas outlet to float the glass blocks. By adjusting and setting the separation interval of the molten glass blocks, a flat spherical preform is obtained.

[0154] As another example of making a preform (Production Example 2), there is a method as follows: after casting a homogeneous molten glass obtained by melting the prepared raw materials into a mold and forming it, the strain of the obtained molded body is removed by annealing, the molded body is cut or severed to divide it into a given size and shape to make a plurality of glass sheets, the glass sheets are polished to make the surface smooth, and a preform made of glass of a given mass is made.

[0155] In each of the above-mentioned examples, a preform for precision press molding was produced by Production Example 2. The melting temperature when the prepared raw materials were melted was set to 1000° C. or higher and 1300° C. or lower.

[0156] For the above-mentioned embodiments, a carbon-containing film was coated on the surface of the preforms, respectively, and the preforms were introduced into a pressing mold made of SiC, which includes an upper and lower mold and a shell mold and has a carbon-containing mold release film on the molding surface. The molding mold and the preforms were heated together in a nitrogen atmosphere to soften the preforms, and precision pressing was performed to produce various lenses (aspherical convex meniscus lens, aspherical concave meniscus lens, aspherical biconvex lens, aspherical biconcave lens) made of the above-mentioned various glasses. The various lenses produced in this way were observed, and as a result, no scratches, blurring, or damage were observed on the lens surface.

[0157] Finally, the above-mentioned embodiments are summarized.

[0158] [1] An optical glass, wherein:

[0159] In the glass composition expressed in mass %,

[0160] The B2O3 content is 15.00 mass % or more and 33.00 mass % or less,

[0161] The ZnO content is 6.00 mass % or more and 18.00 mass % or less,

[0162] Li2O content exceeds 0.00% by mass,

[0163] The Y2O3 content is 3.00 mass % or more and 23.00 mass % or less,

[0164] The total content of Ta2O5+Nb2O5+Bi2O3+TiO2+WO3 (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is 0.00 mass % or more and 0.30 mass % or less,

[0165] The total content RE of La2O3, Gd2O3 and Y2O3 is 43.00 mass % or more and 58.00 mass % or less,

[0166] The mass ratio of the total content RE to the total content of ZrO2, Ta2O5, Nb2O5 and WO3 (RE / (ZrO2+Ta2O5+Nb2O5+WO3)) is 2.00 or more and 13.00 or less,

[0167] The mass ratio of the total content RE to the content of ZnO (RE / ZnO) is 3.80 or more.

[0168] The optical glass has a refractive index nd of 1.750 or more and 1.790, and an Abbe number νd of 47.5 or more and 50.5 or less.

[0169] [2] The optical glass according to [1], wherein:

[0170] The mass ratio of Li2O to SiO2 content (Li2O / SiO2) exceeds 0 and is equal to or less than 1.00.

[0171] [3] The optical glass according to [1] or [2], wherein:

[0172] The total content of LiO 2 and ZnO (LiO 2 + ZnO) is 7.00 mass % or more and 19.00 mass % or less.

[0173] [4] The optical glass according to any one of [1] to [3], which has a glass transition temperature Tg of lower than 640°C.

[0174] [5] The optical glass according to any one of [1] to [4], wherein the degree of coloration λ 80 Below 510nm.

[0175] [6] The optical glass according to any one of [1] to [5], wherein

[0176] The mass ratio of Li2O to SiO2 content (Li2O / SiO2) is greater than 0 and less than 1.00,

[0177] The total content of LiO2 and ZnO (LiO2+ZnO) is 7.00 mass % or more and 19.00 mass % or less,

[0178] The optical glass has a glass transition temperature Tg lower than 640°C and a coloring degree λ 80 Below 510nm.

[0179] [7] An optical element made of the optical glass described in any one of [1] to [6].

[0180] It should be understood that the embodiments disclosed herein are all exemplary and do not constitute limitations. The scope of the present invention is defined by the claims rather than the above description, and is intended to include all modifications within the meaning and scope equivalent to the claims.

[0181] For example, the optical glass of one embodiment of the present invention can be obtained by adjusting the composition described in the specification with respect to the glass composition exemplified above.

[0182] Furthermore, it is of course possible to arbitrarily combine two or more of the items exemplified or described as the preferred range in the specification.

Claims

1. An optical glass, wherein in the glass composition expressed in mass %, The B2O3 content is 15.00 mass % or more and 33.00 mass % or less, The ZnO content is 6.00 mass % or more and 18.00 mass % or less, Li2O content exceeds 0.00% by mass, The Y2O3 content is 3.00 mass % or more and 23.00 mass % or less, The total content of Ta2O5, Nb2O5, Bi2O3, TiO2 and WO3 (Ta2O5+Nb2O5+Bi2O3+TiO2+WO3) is 0.00 mass% or more and 0.30 mass% or less, The total content RE of La2O3, Gd2O3 and Y2O3 is 43.00 mass % or more and 58.00 mass % or less, The mass ratio of the total content RE to the total content of ZrO2, Ta2O5, Nb2O5 and WO3 (RE / (ZrO2+Ta2O5+Nb2O5+WO3)) is 2.00 or more and 13.00 or less, The mass ratio of the total content RE to the content of ZnO (RE / ZnO) is 3.80 or more. The optical glass has a refractive index nd of 1.7500 or more and 1.7900 or less, and an Abbe number νd of 47.50 or more and 50.50 or less.

2. The optical glass according to claim 1, wherein: The mass ratio of the Li2O content to the SiO2 content (Li2O / SiO2) exceeds 0 and is equal to or less than 1.

00.

3. The optical glass according to claim 1, wherein: The total content of LiO 2 and ZnO (LiO 2 + ZnO) is 7.00 mass % or more and 19.00 mass % or less. The optical glass according to claim 1 , wherein the glass transition temperature Tg is lower than 640° C.

5. The optical glass according to claim 1, wherein the coloring degree λ 80 Below 510nm.

6. The optical glass according to claim 1, wherein: The mass ratio of the Li2O content to the SiO2 content (Li2O / SiO2) is greater than 0 and less than 1.00, The total content of LiO2 and ZnO (LiO2+ZnO) is 7.00 mass % or more and 19.00 mass % or less, The optical glass has a glass transition temperature Tg lower than 640°C and a coloring degree λ 80 Below 510nm.

7. An optical element made of the optical glass according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Glass, glass blank for press-forming, optical element blank, and optical element

    JP2018065747A